(untitled) (Ágora Journal, 2022)
In this paper we analyze how the public image of Domitian, the last emperor of the Flavian dynasty (69-96), was constructed based on the Ludi Saeculares that occurred in 88, taking as documentation the coins minted in Rome about the event. We used the concepts of representations and practices by Roger Chartier (2002) and of propaganda applied to Classical Studies by Paulo Martins (2011) and by Ana Teresa Marques Gonçalves (2013). The methodology adopted was that of Content Analysis, by Laurence Bardin (2011). We conclude that the emperor, beyond divine reverences, was represented as a ruler with a policy based on liberalitas and on proximity with the Augustan period.